Comicidade, ironia e humour em Lira dos vinte anos, de Álvares de Azevedo - Santos, Carolina Frizzera (2017)
Humor was a facet of Romanticism that was quite explored here in Brazil, in the middle of the 19th century. Among many young poets, who adventured themselves about this terrain, Álvares de Azevedo stands out because of his diversified literary production: he used humor in various aspects in the Second Part of Lira dos vinte anos. He also could place, inside brazilian literature, the “english and german humor”, or humour, that never before made an appearance in the tropics. This work seeks, from the analysis of poems belonging to the Second Part of his famous book, to explain how the comedy, the irony and the humour appears on Azevedo’s work chosen as corpus. For such analysis, are used as theoretical and critical input works and texts concerning the romantic movement, studies about Álvares de Azevedo’s work and its peculiarities and studies about humor. Some of these works are: Antonio Candido’s Formação da literatura brasileira: momentos decisivos; Jacob Guinsburg’s O Romantismo; Vagner Camilo’s Risos entre pares; Cilaine Alves’ O Belo e o disforme; Henri Bergson’s O riso; Vladimir Propp’s Comicidade e riso, among others. Finally, I seek to show the importance of the young poet in our literature, exploring the humour on his face Caliban, presented on the Preface to the Second Part of the Lira.